2012
DOI: 10.1587/transcom.e95.b.3067
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Telemedical Tool in an Isolated Island and a Disaster Area of the Great East Japan Earthquake

Abstract: SUMMARYThe present paper has reported a case study of the "Electronic Doctor's Bag" which is a telemedical tool for home-visit medical services using the mobile communications environment in an isolated island and a disaster area hit by the tsunami. Clinical trials performed for 20 patients around a clinic in Miyako Island indicated that the communication functions of the proposed system were highly evaluated by patients as well as medical staffs. However, the system still has room for further improvement in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The telemedical services have been used in the disaster area (Miyako Island) of the Great East Japan earthquake on March 11, 2011. In addition to its applications, but finding showed that it still needs further reform in the operability, portability and mobile communication environment [53]. Currently, telemedicine has applications in telenursing, Telepharmac, telerehabilitation, telephone care, Teletrauma care, Tele counseling and E-learning, telepathology, teleradiology, teledermatology, teleradiology, teledentistry, and teleophthalmology [54].…”
Section: Telemedicinementioning
confidence: 99%
“…The telemedical services have been used in the disaster area (Miyako Island) of the Great East Japan earthquake on March 11, 2011. In addition to its applications, but finding showed that it still needs further reform in the operability, portability and mobile communication environment [53]. Currently, telemedicine has applications in telenursing, Telepharmac, telerehabilitation, telephone care, Teletrauma care, Tele counseling and E-learning, telepathology, teleradiology, teledermatology, teleradiology, teledentistry, and teleophthalmology [54].…”
Section: Telemedicinementioning
confidence: 99%
“…Two reviews stated that the appropriate use of telemedicine is crucial for risk management and emergency nursing practice during earthquakes (18,19). Existing studies reported that telemedicine was used to assist plastic surgery, paraplegics, cardiopulmonary medicine, intensive care and other medical treatments during earthquake relief (20)(21)(22)(23)(24). Despite some authors developed telemedicine systems to support treatments and interventions (25)(26)(27), studies on the use of telemedicine for mental health in earthquake settings are limited.…”
Section: Introductionmentioning
confidence: 99%